La importancia del actor social: Un análisis del capital social en el ejido Emiliano Zapata en Amecameca, Estado de México - Díaz Morales, Andrés; De la Fuente Hernández, Juan; Roldán Hernández, Remedios Reymundo (Pontificia Universidad Católica del Perú, 2025)
In recent years, the concept of social capital has been taken up again to analyze human and social relationships. Social capital is manifested in networks of trust, cooperation and informal norms. This resource, influenced by exogenous factors and the agency of the actors, is key to community well-being. Using the methodology of social network analysis and integrating elements of presence of trust and social norms, in addition to the relevance of social actors, the necessary data was obtained. The analysis reveals that the ejido Emiliano Zapata work group functions as a community cohesive by personal ties and values, rather than by formal rules. Between 2012 and 2022, although the number of members decreased, the density of social relationships and trust increased. Key actors play a fundamental role, connecting the group with the outside world and helping to stabilize the organization through self-management and community norms.

En los últimos años, se ha retomado el concepto de capital social para analizar relaciones humanas y sociales. El capital social se manifiesta en redes de confianza, cooperación y normas informales. Este recurso, influenciado por factores exógenos y la agencia de los actores, es clave para el bienestar comunitario. Mediante la metodología de análisis de redes sociales e integrando elementos de presencia de confianza y normas sociales, además de la relevancia de actores sociales, se obtuvieron los datos necesarios para la investigación. El análisis revela que el grupo de trabajo del ejido Emiliano Zapata funciona como una comunidad cohesionada por lazos personales y valores, más que por reglas formales. Entre 2012 y 2022, aunque disminuyó el número de integrantes, aumentó la densidad de relaciones sociales y la confianza. Los actores clave juegan un papel fundamental, conectando al grupo con el exterior y ayudando a estabilizar la organización mediante la autogestión y normas comunitarias.
The Importance of the Social Actor: An Analysis of Social Capital in the Emiliano Zapata Ejido in Amecameca, State of Mexico
Keywords: Social networking; Community well-being; Self-management; Agency; Trust; Redes sociales; Bienestar comunitario; Autogestión; Agencia; Confianza; https://purl.org/pe-repo/ocde/ford#5.04.00